Causal recipes for turning fin-tech freelancers into smart entrepreneurs; Recetas causales para transformar a los profesionales libres fin-tech en emprendedores inteligentes - Daniela Damian; Ciprian Manea (Journal of Innovation & Knowledge (JIK), 2019)
Purpose The purpose of this paper is to explore the extent to which fin-tech freelancers are interested in further development of their own business and receive funding for launching and upscaling their start-up. Design/methodology/approach Using a fuzzy set qualitative comparative analysis (fsQCA), this study examines how experience in dealing with different fin-tech solutions, online reputation, innovation, capabilities and interest to apply for funding affect the desired outcome: turning freelancing services into entrepreneurial initiatives. Findings Fin-tech enables freelancers to become smart entrepreneurs and tailors their experience to capture entrepreneurial opportunities allowing them to apply for funding to a large range of instruments. Research limitations/implications The study was limited to a small sample of fin-tech entrepreneurs and the generalization of results calls for caution. Originality/value A configurational framework aiming to turn fin-tech freelancers into entrepreneurs is proposed, which encompasses the antecedent conditions of personal experience, reputation, innovation and commitment to find money for creating start-ups.
Keywords: L26; J24; 650; Entrepreneurship; Fin-tech; Freelancing; Innovation; Reputation